2020
DOI: 10.1158/0008-5472.bcd-19-0039
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Drug-Resistant Leukemic Stem Cells and Impaired NK Cell Immunity in CML Patients Depend on MIR300 Antiproliferative and PP2A-Activating Functions

Abstract: Persistence of drug-resistant quiescent leukemic stem cells (LSC) and impaired natural killer (NK) cell immune response account for relapse of chronic myelogenous leukemia (CML). Inactivation of protein phosphatase 2A (PP2A) is essential for CML-quiescent LSC survival and NK cell antitumor activity. Here we show that MIR300 has antiproliferative and PP2A-activating functions that are dose dependently differentially induced by CCND2/CDK6 and SET inhibition, respectively. MIR300 is upregulated in CML LSCs and NK… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 70 publications
(100 reference statements)
0
35
0
Order By: Relevance
“…In the rapidly evolving genomic era of precision medicine, a transition towards dynamic monitoring of tumor molecular characteristics is being witnessed. In this regard, easily accessible markers that would reflect the entire heterogeneity of the tumor such as liquid biopsy including CTCs, circulating tumor-derived DNA (ctDNA), plasma cell-free DNA (cfDNA), microRNAs (miRNA), and exosomes have emerged as biomarkers with immense potential (Bronkhorst et al, 2019;Cervena et al, 2019;Silvestri et al, 2020). Plasma cfDNA facilitates non-invasive peripheral blood sampling of tumor-associated actionable alterations that are present in its ctDNA fraction and is gradually finding clinical utility in several cancers.…”
Section: Mrd Assessment In Aml and Current Challengesmentioning
confidence: 99%
“…In the rapidly evolving genomic era of precision medicine, a transition towards dynamic monitoring of tumor molecular characteristics is being witnessed. In this regard, easily accessible markers that would reflect the entire heterogeneity of the tumor such as liquid biopsy including CTCs, circulating tumor-derived DNA (ctDNA), plasma cell-free DNA (cfDNA), microRNAs (miRNA), and exosomes have emerged as biomarkers with immense potential (Bronkhorst et al, 2019;Cervena et al, 2019;Silvestri et al, 2020). Plasma cfDNA facilitates non-invasive peripheral blood sampling of tumor-associated actionable alterations that are present in its ctDNA fraction and is gradually finding clinical utility in several cancers.…”
Section: Mrd Assessment In Aml and Current Challengesmentioning
confidence: 99%
“…However, certain stem cell classes, especially pre-leukemic neoplastic stem cells may be resistant because they are slowly cycling cells and exhibit multiple forms of stem cell resistance ( Valent et al, 2012 ; Valent et al, 2013 ). TKI-resistance of CML LSC has been associated to both cell-autonomous ( Corbin et al, 2011 ; Kumari et al, 2012 ) and extrinsic factors ( Arrigoni et al, 2018 ; Zhang et al, 2018 ; Silvestri et al, 2020 ). Sometimes even LSC may survive TKI therapy and thus persist in CML patients.…”
Section: Introductionmentioning
confidence: 99%
“…One report has shown the involvement of microRNAs in TKI sensitivity in CML LSC ( Salati et al, 2017 ). Recent evidence has shown that miR-300 is a tumor suppressor microRNA able to induce quiescence in CML LSCs ( Silvestri et al, 2020 ), and that miR-126-3p regulates quiescence, self-renewal and engraftment capacity of CML LSCs ( Zhang et al, 2018 ). Advances in the characterization of aberrant expression of surface markers have allowed the prospective isolation of LSC and HSC from CML patients ( Herrmann et al, 2014 ; Warfvinge et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…As noted by Silvestri and colleagues (1), chronic myelogenous leukemia (CML) treatment does not result in cured disease for many patients (2,3). Thus, therapeutic challenges remain.…”
mentioning
confidence: 99%
“…It will be of interest to see how more stringent low oxygen assessments might affect the results reported by Silvestri and colleagues (1) and others for LS/ICs and other CS/ICs in terms of ex vivo growth characteristics, gene and protein expression patterns, and responsiveness to agents used to modulate these activities for eventual health benefit. More importantly, will this and the studies of Silvestri and colleagues (1) eventually be able to be used in a clinical setting?…”
mentioning
confidence: 99%